2021
DOI: 10.3390/endocrines2020013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Subclinical Cardiovascular Damage in Essential Hypertension

Abstract: Vitamin D deficiency is linked to cardiac dysfunction, vascular remodeling, metabolic syndrome and insulin resistance (IR). The aim of the present study was to evaluate the association between vitamin D levels and cardiovascular (CV) organ damage in a large cohort of newly diagnosed treatment-naïve hypertensive patients, and the role of IR in this context. We enrolled 500 Caucasian individuals, without CV or renal complications. Subjects underwent a complete evaluation and measurements of vitamin D, standard l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The factors associated with vitamin D deficiency in the present study were similar to those found in the literature. Indeed, Magurno [16] and Fondio [17] respectively reported in their studies that high blood pressure was associated with vitamin D deficiency. The association between cardiovascular diseases and vitamin D deficiency has been explained by some authors.…”
Section: Discussionmentioning
confidence: 98%
“…The factors associated with vitamin D deficiency in the present study were similar to those found in the literature. Indeed, Magurno [16] and Fondio [17] respectively reported in their studies that high blood pressure was associated with vitamin D deficiency. The association between cardiovascular diseases and vitamin D deficiency has been explained by some authors.…”
Section: Discussionmentioning
confidence: 98%
“…The introduction of the active form of vitamin D helps to reduce this remodeling due to the effect on the functional, anatomical, molecular, and genetic aspects of hypertrophy and dysfunction of cardiomyocytes. A study conducted on newly diagnosed treatment-naïve hypertensive patients showed that hypovitaminosis D was a strong predictor of increased left ventricular mass index [9].…”
Section: Biological Role Of Vitamin Dmentioning
confidence: 99%
“…In VDR knockout animal models, cardiomyocytes develop hypertrophy and cardiomegaly [47,48]. A study conducted on newly diagnosed treatment-naïve hypertensive patients, showed that hypovitaminosis D was a strong predictor of increased left ventricular mass index [49]. By interfering with collagen and metalloproteinase production, vitamin D can also affect the heart extracellular matrix.…”
Section: Vitamin D and Heart Failurementioning
confidence: 99%